2019
DOI: 10.1590/0100-3984.2018.0073
|View full text |Cite
|
Sign up to set email alerts
|

The role of percutaneous transhepatic biliary biopsy in the diagnosis of patients with obstructive jaundice: an initial experience

Abstract: Objective: To evaluate the accuracy of percutaneous transhepatic biliary biopsy (PTBB) in patients with suspected biliary obstruction. Materials and methods: This was a retrospective analysis of 18 patients with obstructive jaundice who underwent PTBB. In each patient, three to ten fragments were collected from the lesion. The final diagnosis was confirmed in the pathology report. We also reviewed analyses of the results of laboratory tests performed before the procedure, as well as the Bismuth classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
0
11
0
7
Order By: Relevance
“…Evaluation of the liver by imaging methods has been the subject of various recent studies in the radiology literature of Brazil (28)(29)(30)(31)(32) . The availability of affordable, good quality ultrasound machines has allowed the development of focused point-of-care ultrasound protocols applicable to tropical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the liver by imaging methods has been the subject of various recent studies in the radiology literature of Brazil (28)(29)(30)(31)(32) . The availability of affordable, good quality ultrasound machines has allowed the development of focused point-of-care ultrasound protocols applicable to tropical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the radiology literature of Brazil have emphasized the importance of imaging examinations in the evaluation of hepatic neoplasms (18)(19)(20)(21)(22)(23) . The present study used the LI-RADS classification system to analyze 38 patients infected with hepatitis viruses (HBV, HCV, HDV, or combinations thereof) who underwent CT. We found that approximately 32% of the patients presented with LI-RADS 5 observations (i.e., lesions diagnosed by imaging as classic HCC).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transluminal forceps biopsy (PTFB) of the bile duct performed during PTBD was first reported in 1980 ( 10 ) , and several studies have since demonstrated its safety and sensitivity, especially in cases of cholangiocarcinoma. Nevertheless, this technique is neither cited nor recommended in the ESMO guidelines ( 8 ) , probably because all published reports have involved only a small number of cases and the level of evidence therefore remains low ( 1 , 2 , 10 - 14 ) . To our knowledge, there have been no studies analyzing the safety and efficacy of PTFB in patients with metastatic biliary involvement.…”
Section: Introductionmentioning
confidence: 99%